Sociocultural representations and attitudes related to dementia in Central Africa and in Limousin (France) - (:unkn) unknown (My University, 2013)
Introduction: Dementia is a huge public health problem. Its sociocultural representations vary depending cultures. The impacts these representations have on behaviors and attitudes need to be studied. We aim at describing perceptions and representations people have in Central Africa and in Limousin, in particular concerning public stigma. Method: Cross-sectional surveys were carried out in two capitals of Central Africa (Bangui, Central African Republic, and Brazzaville, Republic of Congo) and in Limousin (Creuse, France). The Explanatory Model Interview Catalogue was used to conduct 549 interviews in Central Africa, and make a questionnaire to assess Alzheimer’s disease-related public stigma.This was filled in by 458 persons in Creuse. Results: In Cetral Africa, the biomedical concept of dementia is generally unknown. But the phenomenon is perceived andrefers for many people to normal ageing. Perceived stigma relies on ambivalent representations of elderly people (magical-religious beliefs). Nevertheless, it is limited by social values deeply rooted in people’s mind. In Limousin, stigma is more perceived by health caregivers and youths.Conclusion: Dementia is a stigmatizing illness. More reflections and actions are necessary to help affected people in the best way
Keywords: African Research